Motor vehicle insurance android application for Minerva - Gono, Davison Rungano (Midlands State University, 2017)
The need to provide a solution to help client of Minerva Risk advisors necessitated the creation of this project and the documentation. It is divided into five chapters which are Introduction, Planning, Analysis, Design and Implementation. A background of the study and feasibility of the project are found in the first two chapters of this document showing detail on the organisation and feasibility of the project. Analysis, design and Implementation follow, these are detailed with system analysis, the proposed systems design and how it is to be implemented by the developer. Use of diagrams is evident to help emphasize and to make aspect understandable. The system was designed using Android studio, Xampp and PHP.